Pengendalian Kualitas Produk Dengan Menggunakaan Statistical Processing Control (Spc) Pada PT Surya Teknologi - Yoga Yolanda Amarta; Hazimah Hazimah (LPPM Universitas Putera Batam, 2020)
PT Surya Teknologi is company producing elektronic .intence competition forced the management to make a conpet plan to deal with it.this cause each company triying to produce a batter electronic to give satisfaction to the consumer. In this research the method of analysis used is Statistical Process Control, which is a statistical method used to measure the extent of quality control process performed on a company, where the results are compared with the standards applied by the company. The result of this research shows that product quality control at PT Surya Teknologi is still uncontrolled. With an average damage of 7.93%. The most common type of damage is Selentetd with a total of 1633 of total defective products in 2017. From fieldobservations and interviews, the factors causing this damage are human factors, machinery, environment, working methods and materials.